PENGARUH KUALITAS PELAYANAN, PROMOSI DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOTOR DI DEALER SUZUKI PT MAHKOTA INTI SEJAHTERA JAKARTA - Ogi Suwardi; Rani Hamzah (Jurnal Ekonomi Bisnis Indonesia, 2022)
Abstract: This study aims to determine the influence of service quality, promotion and price toward purchase decision of motorcycle at Dealer Suzuki PT MAHKOTA INTI SEJAHTERA JAKARTA. The method used in this study is descriptive and verification with quantitative approach with the number of samples of 98 respondents. The results showed that independently the quality of service and promotion significantly influence purchasing decisions while prices have no significant effect on purchasing decisions. While simultaneously (variable) quality of service, promotion and price have a significant effect to purchasing decision. While the value of R is 0.802 close to 1, indicating there is a strong enough influence between independent variables to the dependent variable. The result of Adjusted R Square Analysis (Adj.R2) 0.631, showing the variable of service quality, promotion and price have influence to motorcycle purchasing decision at Suzuki Dealer PT Mahkota Inti Sejahtera Jakarta for 63.1% while the rest equal to 36.9% influenced by other variable outside this research.